KAJIAN PENGELOLAAN DANA OTONOMI KHUSUS DI KABUPATEN ASMAT - Anthonius H. Citra Wijaya (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2016)
The aims of this study were to: (1) identify and review issues and aspects in financial planning and management of Special Autonomy Fund in delivering education and health services as well as formulate alternative policies to improve financial planning and management funded by Papua Special Autonomy Fund in Asmat regency. A case study approach was applied in this study using multiple case designs. Population to be observed in this study was the whole social organization, government offices and legislative institutions located in the regency of Asmat. The sampling technique used was multistage non random sampling. The results showed low level of accountability in reporting the use of Special Autonomy Funds. This pointed out the lack of desire from Asmat regency for implementation of transparency of financial reporting. Lack of transparency in the use of special autonomy funds could negatively impact at large scales which could be detrimental to societies, particularly in the Asmat regency. Special Autonomy Fund allocation for the education sector was not complied with the mandate of Special Regional Regulation No. 25 in 2013 titled Revenue Distribution and Financial Management of the Special Autonomy Fund. The education sector was being allocated for the fund 27.03 per cent on average despite the regulation mandate which was 30 per cent. On the other hands, the special autonomy fund allocation for health sector was complied with the regulation which was 15 per cent. Key Words: Papua, Asmat, Special Autonomy Fund